Komponen dan Faktor Penentu Biaya untuk Penetapan Tarif Angkutan Kereta Api Barang - Handayani Handayani (EBBANK, 2015)
The train has many advantages compared to other modes of transport, among other things: a relatively large load capacity in all transport, production costs are relatively efficient, as well as the accuracy and speed of travel, especially those who have had multiple lines. In addition the use of rail transport can avoid the cost of road repairs due to freight trains can be avoided load exceeds the capacity. In order to increase the share of rail transport necessary goods tariff guidelines that can be used both by regulators, operators, and users of goods rail transportation services. This is because since 2012 the Minister of Transport Regulation No. 34 Year 2011 concerning Procedures for Calculation and Determination of Rates Transport Persons and Goods By Train has been replaced by the Regulation of the Minister of Communications No. 28 Year 2012 on Guidelines Calculation and Determination of Rates Transport People By Train. In this study, carried out the study in addition to the existing rules, also conducted field research to determine the cost of components and the cost of any decisive factor to be reckoned as a guideline tariff rail transport of goods.